PERIPHERAL NERVE NEUROMA ULTRASTRUCTURE AFTER INJURY AND OPERATIVE TREATMENT USING HIGH-FREQUENCY ELECTROSURGICAL TECHNOLOGY WITH PHARMACOLOGICAL CORRECTION - Korsak, A.; Likhodiievskyi, V.; Kryvosheyeva, O.; Chernets, V.; Chaikovskyi, Yu. (World of Medicine and Biology, 2015)
The article consideres the new original method of peripheral nerves injury treatment with further pharmacological correction. After peripheral nerve injury experimental modeling on rats we performed nerve stumps joining using high-frequency electric welding technology with further Traumel C administration. After injured nerve’s regenerative neuroma’s ultrastructural analysis we estimate positive influence of electrosurgical device application for nerve injuries treatment both with Traumec C administration in postoperative period due to degeneration enhancement and early regeneration promotion at trauma site.
Keywords: electrosurgical welding; peripheral nerve injury; Traumel S